Sekawan Teruna / Mohamad Azhar Ahawan and Mohamad Ehsan Ikhwan Mohamad Ali - Ahawan, Mohamad Azhar; Mohamad Ali, Mohamad Ehsan Ikhwan (2023)
Sekawan Teruna is a clothing company that specializes in printed tea patterns. The brand's name means "four friends" in Malay, and it is inspired by the close friendship of the four brothers who founded the company. Sekawan Teruna is known for its classic and timeless designs, which are made from high-quality materials. The brand's target market is men of all ages who appreciate quality and style. Sekawan Teruna is based in Pasir Mas and mostly conducts business online. The company understands the value of having a social media presence, and it uses Facebook to market and sell its products. The Facebook page regularly publishes content and engages users directly through Facebook Messenger and WhatsApp. Efficient delivery services are crucial to the brand's success, and it has partnered with J&T Malaysia, a reliable and fast delivery service. Customer satisfaction is a top priority for the brand, and it is achieved by offering a wide selection of quality products and excellent service. Through this social media portfolio, Sekawan Teruna outlines how its business determines its objectives and thorough plan in accomplishing target goals by studying the strategy in terms of marketing, which includes soft sell and hard sell to tempt customers. All of these elements are addressed throughout the report with detailed explanations regarding the business.